Virus-like particles as carriers for T-cell epitopes: limited inhibition of T-cell priming by carrier-specific antibodies. - Ruedl, C; Schwarz, K; Jegerlehner, A; Storni, T; Manolova, V; Bachmann, M (2005)
Virus-like particles (VLPs) are able to induce cytotoxic T-cell responses in the absence of infection or replication. This makes VLPs promising candidates for the development of recombinant vaccines. However, VLPs are also potent inducers of B-cell responses, and it is generally assumed that such VLP-specific antibodies interfere with the induction of protective immune responses, a phenomenon summarized as carrier suppression. In this study, we investigated the impact of preexisting VLP-specific antibodies on the induction of specific cytotoxic T-cell and Th-cell responses in mice. The data show that VLP-specific antibodies did not measurably reduce antigen presentation in vitro or in vivo. Nevertheless, T-cell priming was slightly reduced by antigen-specific antibodies; however, the overall reduction was limited and vaccination with VLPs in the presence of VLP-specific antibodies still resulted in protective T-cell responses. Thus, carrier suppression is unlikely to be a limiting factor for VLP-based T-cell vaccines.